Volume 6: 33rd International Conference on Design Theory and Methodology (DTM) 2021
DOI: 10.1115/detc2021-68723
|View full text |Cite
|
Sign up to set email alerts
|

Quantifying the Predictive Abilities of Speculative Fiction: A Feasibility Study

Abstract: In this article, we explore the capability of speculative fiction to predict future realized technologies. We review a large set of speculative technologies introduced in speculative fiction to determine if the technologies were subsequently realized. Additionally, we explore the time between the speculated introduction and actual realization. Our dataset for analysis is built from the ‘Technovelgy’ database of speculative technologies. A realization assessment methodology is created that includes detailed rub… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(5 citation statements)
references
References 0 publications
0
5
0
Order By: Relevance
“…How good is ChatGPT at knowledge discovery of a technical nature from non-technical content such as mining speculative technologies from a given text as compared to humans? To answer these questions, we designed two experiments based on a previous study completed in 2021 (Xu et al 2021). Researchers have explored the potential of leveraging science fiction narratives to enhance designers' ideation processes (Sterling 2005;Bleecker 2009;Dunne and Raby 2013;Callaghan 2015;Kotecha et al 2021).…”
Section: Methodsmentioning
confidence: 99%
See 4 more Smart Citations
“…How good is ChatGPT at knowledge discovery of a technical nature from non-technical content such as mining speculative technologies from a given text as compared to humans? To answer these questions, we designed two experiments based on a previous study completed in 2021 (Xu et al 2021). Researchers have explored the potential of leveraging science fiction narratives to enhance designers' ideation processes (Sterling 2005;Bleecker 2009;Dunne and Raby 2013;Callaghan 2015;Kotecha et al 2021).…”
Section: Methodsmentioning
confidence: 99%
“…We then employed five human raters to determine if the technologies were realized so that each technology was reviewed by three different human raters. Further details about this study can be found in a previous paper (Xu et al 2021).…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations